2013
DOI: 10.4317/jced.51188
|View full text |Cite
|
Sign up to set email alerts
|

True vertical validation in facial orthognathic surgery planning

Abstract: Objectives: To validate the effectiveness of the original standards of True Vertical (TV) Subnasal Line in orthognatic surgery planning. The present study evaluates the changes occurring in patients with skeletal Class II alterations programmed for orthognathic surgery with a view to improving their facial profile. Study design: We showed a series of black profiles (composed by a first control group of subjects with normal occlusion, and another two additional groups comprised patients before –Group 2- and aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 26 publications
(36 reference statements)
1
8
0
Order By: Relevance
“…In the Espinar study (class II patients), only horizontal displacements of points Ils and Pog’ had the most effect on the profile. 8 In the present study, we observed that the higher the B point, the lower the PNS point, and the more the anterior point A, the better the profile would be. In the study of Marchiori et al , participants’ profile was not correlated with magnitude of NLA angle.…”
Section: Discussionsupporting
confidence: 51%
See 2 more Smart Citations
“…In the Espinar study (class II patients), only horizontal displacements of points Ils and Pog’ had the most effect on the profile. 8 In the present study, we observed that the higher the B point, the lower the PNS point, and the more the anterior point A, the better the profile would be. In the study of Marchiori et al , participants’ profile was not correlated with magnitude of NLA angle.…”
Section: Discussionsupporting
confidence: 51%
“…In Espinar et al's research (Class II patients), the highest displacements were in the lower third of the face; and Ils, Li, and Pog' points showed the most significant changes (horizontal dimension). 8 In a study by Altung Atac et al (double-jaw surgery for Class III patients), the most changes were in the horizontal and vertical dimensions in the mentolabial angle and the chin. On the other hand, nose and upper lip areas had the least changes in these surgeries and questioned the necessity of maxillary surgery in the patients.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Compared to other reference lines for the lip position, the E-line appears very convenient due to its anterior location, although it has limitations in terms of consistency and sensitivity 37 . Therefore, the true vertical subnasal line may be preferable, due to its independence from the position of the chin and also because it overcomes the limitations of other reference planes 38 . Future studies should include this type of reference for sagittal aesthetic measurements.…”
Section: Discussionmentioning
confidence: 99%
“…-To account for the transversal and vertical dimensions of treatment with their relative functional importance. This is being proposed more often and allows a more systematic correction even for slight anomalies 15,21,26,30 .…”
Section: Treatment Planmentioning
confidence: 99%